Adapting the Ryff Scales of Psychological Well-being: a 28-Item Vietnamese Version for University Students - Raul Calderon Jr; Nguyen Thi Nga; Truong Quang Tien; Bui Thi Tu Quyen; Nguyen Hoang Minh Thuan; Vu Viet Bao, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Research in psychological well-being and correlates to general health have blossomed in the last 20-25 years. However, little research exists in health and psychological well-being of the Vietnamese population, partially due to a lack of valid and reliable research instruments available in the Vietnamese language. This study aimed to produce a short, valid and reliable research instrument in Vietnamese to assess the psychological well-being of university students. The 54-item Ryff Scales of Psychological Well-being (RSPWB), a widely used and validated instrument, was the instrument of choice. A research questionnaire, which included the RSPWB, was translated and completed by 253 Vietnamese undergraduate students (18-27 years of age). Analyses included the use of partial least squares, structural equation modeling (PLS-SEM) - a second generation statistical technique for testing complex path models, to evaluate the validity and reliability of the 54 items. As a result of the research, the PLS-SEM analyses produced a multidimensional model with six factors (autonomy, environmental mastery, purpose in life, personal growth, positive relations with others, and self-acceptance) and 28 items that demonstrated good convergent and discriminant validity and reliability. Moreover, the 28-item Vietnamese version of the RSPWB supported the same multidimensional six-factor structure as proposed in the original RSPWB. In conclusion, the adapted 28-item Vietnamese version of the RSPWB is shorter in length, has good psychometric properties, and helps to fill a current gap of available research instruments for advancing the current understanding of psychological well-being and relationships to health in Vietnamese university students. Received: 6th January 2019 ; Revised 15th April 2019; Accepted 23rd April 2019